3D‐printed patient individualised models vs cadaveric models in an undergraduate oral and maxillofacial surgery curriculum: Comparison of student's perceptions. (14th March 2020) - Seifert, Lukas B.; Schnurr, Benedikt; Herrera‐Vizcaino, Carlos; Begic, Amira; Thieringer, Florian; Schwarz, Frank; Sader, Robert
Abstract: Background: Recent advances in 3D printing technology have enabled the emergence of new educational and clinical tools for medical professionals. This study provides an exemplary description of the fabrication of 3D‐printed individualised patient models and assesses their educational value compared to cadaveric models in oral and maxillofacial surgery. Methods: A single‐stage, controlled cohort study was conducted within the context of a curricular course. A patient's CT scan was segmented into a stereolithographic model and then printed using a fused filament 3D printer. These individualised patient models were implemented and compared against cadaveric models in a curricular oral surgery hands‐on course. Students evaluated both models using a validated questionnaire. Additionally, a cost analysis for both models was carried out. P ‐values were calculated using the Mann‐Whitney U test. Results: Thirty‐eight fourth‐year dental students participated in the study. Overall, significant differences between the two models were found in the student assessment. Whilst the cadaveric models achieved better results in the haptic feedback of the soft tissue, the 3D‐printed individualised patient models were regarded significantly more realistic with regard to the anatomical correctness, the degree of freedom of movement and the operative simulation. At 3.46 € (compared to 6.51 €), the 3D‐printed patient individualised models were exceptionally cost‐efficient. Conclusions: 3D‐printed patient individualised models presented a realistic alternative to cadaveric models in the undergraduate training of operational skills in oral and maxillofacial surgery. Whilst the 3D‐printed individualised patient models received positive feedback from students, some aspects of the model leave room for improvement.